Strategi Dalam Mengembangkan Industri Kreatif Sektor Kerajinan Kain Tenun Ulos Silalahi Dengan Tantangan Berinovasi Pada Era Modern Guna Meningkatkan Daya Saing (Studi di Dinas Perindustrian dan Perdagangan Kab. Dairi) - Berutu, Fajran Rahman; Aslami, Nuri (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The purpose of this study is to identify strategies for growing the ulos silalahi woven fabric craft sector's creative industry while addressing the problem of modern innovation to boost the region's competitiveness. This study employs a qualitative methodology that compares literature utilizing technical literature studies, literature studies based on sources, and literature studies based on supporting reference materials. Furthermore, this study makes use of secondary data that is derived from information provided by many relevant organizations or agencies. The Darii Regency is the subject of this study.